2012
DOI: 10.4014/jmb.1107.07028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Colony Morphology with Coenzyme Q10 Production and Its Enhancement from Rhizobium radiobacter T6102W by Addition of Isopentenyl Alcohol as a Precursor

Abstract: Rhizobium radiobacter T6102 was morphologically purified by the aniline blue agar plates to give two distinct colonies; white smooth mucoid colony (T6102W) and blue rough colony (T6102B). The coenzyme Q 10 (CoQ 10) was produced just by T6102W, showing 2.0 mg/g of CoQ 10 content, whereas the T6102B did not produce the CoQ 10. All of the used CoQ 10 biosynthetic precursors enhanced the CoQ 10 production by T6102W. Specifically, the supplementation of 0.75 mM isopentenyl alcohol improved the CoQ 10 concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Using a bacterium, different yeasts, and a filamentous fungus, Kawada et al [ 16 ] demonstrated that the addition of DMAOH, IOH, geraniol (GOH), or mixtures of IOH with either DMAOH or GOH at concentrations of 0.5 mM–1 mM, improves the ubiquinone content of the considered cells by 30 to 72% at the end of the fermentation process. The same was also demonstrated later on using Rhizobium radiobacter [ 17 ] with a cellular increase of 30% in ubiquinone content following the addition in the culture medium of 1 mM IOH. In a completely different type of experiment aiming at the time to discover the late enzymes (genes) of the MEP pathway, it was demonstrated that an insertion in the promotor region of the lytB gene of Synechocystis strain PCC 6803 caused impaired growth and a greenish-yellow phenotype instead of the dark blue-green normal one.…”
Section: Premisessupporting
confidence: 71%
“…Using a bacterium, different yeasts, and a filamentous fungus, Kawada et al [ 16 ] demonstrated that the addition of DMAOH, IOH, geraniol (GOH), or mixtures of IOH with either DMAOH or GOH at concentrations of 0.5 mM–1 mM, improves the ubiquinone content of the considered cells by 30 to 72% at the end of the fermentation process. The same was also demonstrated later on using Rhizobium radiobacter [ 17 ] with a cellular increase of 30% in ubiquinone content following the addition in the culture medium of 1 mM IOH. In a completely different type of experiment aiming at the time to discover the late enzymes (genes) of the MEP pathway, it was demonstrated that an insertion in the promotor region of the lytB gene of Synechocystis strain PCC 6803 caused impaired growth and a greenish-yellow phenotype instead of the dark blue-green normal one.…”
Section: Premisessupporting
confidence: 71%
“…Hence, more coenzyme Q will release the inhibition and improve the production of acetic acid (Table 3). Five precursors of ubiquinone are selected as promoter of fermentation and developed in A. pasteurianus according to Seo et al's work [21]. We used both precursors for Co Q production associated with isoprenoid side chain and benzoquinone ring synthesis [22].…”
Section: Effect Of Different Co Q Precursors On the Starting-up And Amentioning
confidence: 99%
“…2,5,[13][14][15] The specic productivity of CoQ 10 achieved by these metabolically engineered E. coli strains was very low and not comparable to the natural CoQ 10 producers such as R. sphaeroides, A. tumefaciens and R. radiobacter. 16,17 Thus, it seems particularly attractive and practical to directly genetically modify R. sphaeroides and improve upon its intrinsically high CoQ 10 titer.…”
Section: Introductionmentioning
confidence: 99%